Clinical implications of telomere dysfunction in lung fibrosis. Issue 5 (September 2018) - Molina-Molina, Maria; Borie, Raphael
Abstract : Purpose of review: Telomere attrition has been proposed as one of the aging hallmarks in pulmonary fibrosis. Telomere shortening and telomerase gene mutations have been widely evaluated in recent years. Reduced telomere length may be identified in a quarter of patients with sporadic idiopathic pulmonary fibrosis (IPF) and half of those cases with family aggregation. However, telomere studies have not transferred from the research field to the clinic. This review is focused on our current understanding of the pathogenic implication of telomere dysfunction in lung fibrosis and its relevance in the clinical setting. Recent findings: The most prevalent clinical expression of telomere dysfunction is IPF. Disease onset is usually seen at a younger age and family aggregation is frequently present. Short telomere syndrome is associated in a minority of cases and includes premature hair greying, bone marrow failure and liver cirrhosis. However, patients often present with some extrapulmonary associated telomeric features and related comorbidities that may help to suspect telomere defects. Telomere shortening confers a poor prognosis and reduced lung-transplant free survival time in IPF and other nonidiopathic pulmonary fibrotic entities. Summary: Telomere dysfunction associates some common clinical features that could modify patient management in pulmonary fibrosis.